2018
DOI: 10.1186/s12896-018-0421-6
|View full text |Cite
|
Sign up to set email alerts
|

Total RNA extraction from tissues for microRNA and target gene expression analysis: not all kits are created equal

Abstract: BackgroundmicroRNAs (miRNAs) are short non-coding RNAs that fine-tune gene expression. The aberrant expression of miRNAs is associated with many diseases and they have both therapeutic and biomarker potential. However, our understanding of their usefulness is dependent on the tools we have to study them. Previous studies have identified the need to optimise and standardise RNA extraction methods in order to avoid biased results. Herein, we extracted RNA from murine lung, liver and brain tissues using five comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 32 publications
2
69
0
Order By: Relevance
“…However, it is still difficult to quantify the levels of c-miRNAs due to their low concentrations while all the miRNA detection methods depend on the quality of the starting material. In addition, the most widely used methods including qRT-PCR and microarray are based on the assumption that the different RNA extraction methods isolate all miRNAs equally [29]. However, as discussed above the levels of c-miRNA isolated using different methods should not be directly compared as the recovery of c-miRNA varies dramatically [127,128].…”
Section: Detection Methods and Normalization Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still difficult to quantify the levels of c-miRNAs due to their low concentrations while all the miRNA detection methods depend on the quality of the starting material. In addition, the most widely used methods including qRT-PCR and microarray are based on the assumption that the different RNA extraction methods isolate all miRNAs equally [29]. However, as discussed above the levels of c-miRNA isolated using different methods should not be directly compared as the recovery of c-miRNA varies dramatically [127,128].…”
Section: Detection Methods and Normalization Strategiesmentioning
confidence: 99%
“…Additionally, due to their low concentration in plasma and serum, miRNAs can only be quantified using amplification techniques and thus the amount of starting material and the extraction method may affect the results [28]. It has been demonstrated that sample type and processing, as well as RNA extraction methods significantly affect the miRNA profile and/or expression levels [28,29]. Importantly, a comparison of c-miRNA profiles obtained by different laboratories for the same disease, including CVDs, revealed different expression levels of specific miRNAs (see [30] and references cited therein), illustrating the need to standardize the detection and analysis of c-miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Then, total RNA was extracted using the phenol chloroform method (21). The purity of RNA was determined by A260/A280 using ultraviolet spectrophotometry (Nanodrop 2000 Spectrophotometer; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…However no correlations between fold changes in sequencing reads and qPCR abundance for expression of miR‐100‐5p, ‐23b‐5p, and ‐203a were detected. This observed discordance again reflects the uncertainties imposed by different RNA isolation methods, in this study to undertake qPCR analysis, ‐phenol chloroform‐based extraction method was used, differing from the solid‐phase separation with affinity resin based extraction that is necessary for purifying better quality RNA needed for HTS . Further, quantification of miRNA expression by qPCR is influenced by the choice of reference genes used for normalization .…”
Section: Discussionmentioning
confidence: 99%